Conceptual metaphors of morality in Indonesian language: A corpus-based cognitive semantic study - Hasibuan, Nurainun; Mulyadi; Mahriyuni; Nasution, Khairina; Nurlela; Rosa, Rusdi Noor (Research Journal in Advanced Humanities, 2026)
This study examines conceptual metaphors of morality in the Indonesian language using a corpus-based cognitive linguistic approach. Morality, as an abstract value system, is often understood through metaphors rooted in physical and cultural experiences. This study aims to identify and analyze conceptual metaphors of morality. The data consists of 650 sentence samples obtained from the Leipzig Corpora Collection (2020–2024) and analyzed using Sketch Engine through the Metaphoric Pattern Analysis method and Conceptual Metaphor Theory. The results identified 453 metaphorical expressions (69.69%) classified into 25 conceptual metaphors. The findings show that the dominant metaphor is MORALITY IS A BUILDING (26.49%), followed by MORALITY IS SPACE (11.70%) and MORALITY IS CLOTHING (9.71%). This pattern reflects the tendency of Indonesian society to understand morality as a solid yet fragile entity (a building), as a social environment or identity (space and clothing), and as something that can be measured vertically and is potentially vulnerable to damage. This study contributes to metaphor studies in cognitive linguistics by providing empirical data from Indonesia and offering insights into the construction of moral values in contemporary public discourse.